Database Management System in Accounting: Assessing the Role of Internet Service Communication of Accounting System Information - Muhammad Fakhimuddin; Uswatun Khasanah; Rini Trimiyati (Publindo Akademika, 2021)
Data management is part of information resource management which includes all activities that ensure that company data resources are accurate, up-to-date, and safe from tampering, and are also available to users and the company. This study aims to find out about the role of concept database management in managing large volumes of company data. The result showed that data management activities include data collection, integrity, and testing, storage, maintenance, security, organization, retrieval. Meanwhile, the database structure includes hierarchical database structure, network database structure, and relational database structure.